Synthesis and characterization of some biological active transition metal complexes of Schiff base derived from cefixime with mixed ligand 8-hydroxy quinoline (Baghdad Science Journal, 2015)
The aim of the work is synthesis and characterization of bidentate ligand [dipotassium sodium7-((E)-2-(2-((Z)-1-carboxylatoethylideneamino)thiazol-4-yl)-2 (carboxylatemethoxyimino) acet amido)-8-oxo-3-vinyl-5- thia-1-azabicyclo[4.2.0] oct-2- ene-2- carboxylate] [Nak2L], from the reaction of cefixime with sodium pyruvet to produce the ligand [Nak2L], the reaction was carried out in methanol as a solvent under reflux. The prepared ligand [Nak2L] which was characterized by FT-IR, UV-Vis spectroscopy, 1H, 13C-NMR spectra, Mass spectra, (C.H.N) and melting point. The mixed ligand complexes were prepared from ligand [Nak2L] was used as a primary ligand while 8-hydroxy quinoline [Q] was used as a secondary ligand with metal ion M(?).Where M(?) = (Mn ,Co ,Ni ,Cu ,Zn and Cd) at reflux ,using methanol as a solvent, KOH as a base. Complexes of the composition [(M)2(Q)2(KL)(H2O)4] with (2:2:1) molar ratio were prepared. All the complexes were characterized by spectroscopic methods (FT-IR, UV-Vis spectroscopy) along with elemental analysis (A.A), chloride content and melting point measurements were carried out, together with conductivity and magnetic susceptibility. These measurements showed octahedral geometry around (Mn??, Co??, Ni??, Cu??, Zn?? and Cd??) ions. The biological activity of the ligands [NaK2L], [Q] and complexes [(M)2(Q)2(KL)(H2O)4] were studied by using inhibition method.